Establishing a Multidisciplinary Breast Unit in a Middle Income Country â Challenges and Successes - Taib, Nur Aishah; Amiruddin, Alfiah (Indonesian Journal of Cancer, 2008)
The Breast Unit in the University Malaya Medical Centre (UMMC) was set up in 1993 to cater for the increasing number of women presenting with breast complaints. The surgeon plays a central role in the coordination of the multidisciplinary team which consists of the breast surgeon, pathologist, radiologist, oncologist, plastic surgeon, physiotherapist, psychooncologist, as well as the specialist breast care nurse. The unit provides a comprehensive patient care yrogramme, with diagnostic services (triple assessment comprising clinical evaluation, radiological assessment and biopsy), breast screening services (clinical breast examination ana mammography / adjunct ultrasound), oncological services and palliative care services. Throughout the course of the treatment and post-treatment, emphasis is placed on supportive and emotional care of the patient and her relatives. Teaching and training of undergraduate and postgraduate students form part of the functions of this unit, and clinical and basic research is actively carried out. It has been shown that patients treated in a multidisciplinary breast unit have a better overall outcome: however in low and middle income countries, the development of such units are hampered but lack of manpower and resources. In UMMC, with the institution of treatment protocols and guidelines, it is hoped that survival of patients treated in this multidisciplinary unit will progressively improve.Key words : breast cancer, multidisciplinary breast unit, comprehensive breast care